Analisis ergonomi pada perkuliahan daring menggunakan smartphone selama masa pandemi covid-19: studi kasus mahasiswa Prodi Teknik Industri Universitas Mulawarman - Lina Dianati Fathimahhayati; Theresia Amelia Pawitra; Willy Tambunan (Universitas Mercu Buana, 2020)
When Covid-19 emerged in Indonesia in early 2020, students had to learn from home to prevent the spread of the virus. The changing activity could effect on physical and mental health caused by student’s behavior during learning from home. Survey showed that 84% students of Industrial Engineering, Mulawarman University used smartphone while learning from home. Therefore, this study aimed to identify students’ behavior, to measure physical (i.e., musculoskeletal and visual fatique) and mental health (i.e., stress and smartphone addiction) problems that occurred when they were learning from home, as well as to suggest ergonomic recommendation for reducing the negative effects. At the time of the study, they were 155 students studied in the IE department and a total of 134 (86.45%) participated in the online survey. Musculoskeletal disorder was assessed using Nordic Body Map and visual fatique was evaluated using symptoms that were reported on previous studies. Additionally, Smartphone Addiction Scale (SAS) and Perceived Stress Scale (PSS) were administered to identify smartphone addiction tendency and stress level respectively. The results showed that MSD occurred in left and right shoulder (95%), followed by upper neck (82.14%) and back (72.62%). 86% of participants experienced visual fatique with headache (71.55%), ache eye (68%) and dry eye (60.34%) symptoms. Subsequently, this survey revealed that 35% of the participants addicted to smartphone and 68.66% experienced moderate level of stress. To alleviate these physical problems, several ergonomic recommendations were proposed i.e., supporting the arm that holding the smartphone with the other hand, practicing the 20-20-20 rule and applying stop, drop and flop slogan. Moreover, cooperation among parents, students and lecturers was needed to create conducive learning environment so as the mental health problems could be minimized.